ESHRE 2022 Annual Meeting: main topics of science, ethics, and law in the context of reproductive medicine (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
38th Annual Meeting of the European Society of Human Reproduction and Embryology (ESHRE) was held in Milan, 3 – 6 July 2022. ESHRE’s annual conference is a great opportunity of scientific and professional networking, where multidisciplinarity is a key principle. This article aims at providing the reader with a map of the main topics, in the context of reproductive medicine, presented and discussed during the meeting. Scientific innovation, original ethical questions, and significant regulatory recommendations have been addressed.
Keywords: ESHRE 2022; reproductive medicine; ethics and law; IVF; fertility treatment